(untitled) (BioLaw Journal - Rivista di BioDiritto, 2026)
Practicing sports across the lifespan, especially in adolescence, can foster individual growth when supported by aware adults and safe educational environments. Cultural and organizational dynamics may expose minors to pressure, potentially leading to maltreatment or abuse, in both amateur and competitive sports. Specific forms, such as neglect and psychological abuse, are difficult to detect, as they are often denied or minimized by the athletes themselves. It is essential to ensure environments that prioritize well-being and protection of minors’ rights, while increasing awareness of the risks. The presence of adults, understood as non-directive guidance, is crucial to fostering inclusive sporting experiences that support healthy growth.